Trends of Criminal Activity and Substance Use in a Sample of Welfare Recipients - Brown, Victoria L.; Montoya, Isaac D.; Dayton-Shotts, Cheryl A.; Carroll-Curtis, Tiffany L.; Riley, Micah A. (Crime and delinquency, 2004)
The Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) of 1996 instituted a compulsory work mandate for welfare recipients. However, recipients who experience difficulties finding employment may increase their involvement in criminal activities and their frequency of substance use as a means to deal with changes precipitated by PRWORA. This study used a four-wave panel design to analyze the criminal behaviors and substance-use frequency of 534 welfare recipients in Houston, Texas. Data were collected from the Attitudes, Behaviors, and Skills Assessment (ABSA) instrument designed specifically for this study. Results show that a minority of welfare recipients were involved in criminal activity. Furthermore, although participants were losing their welfare benefits, both criminal activity and substance use declined over time.